The theory and practice relation in the teaching of philosophy: A look at philosophical knowledge in public high schools - Gomes, Max Barbosa (Seven Editora, 2023)
This objective scientific article critically analyze the theory and practice relationships in the study of Philosophy in the School of Public Schools. Therefore, we use two state public schools that functioned as research objects. From these observational "locus" we seek to reconstitute the optics of teachers and students and find out how this educational process is carried out concretely in social practice. This analysis was based on the paradigm of critical science supported the theoretical framework of Materialism - history, according to which theory and practice are related dialectically. We hope that the results obtained in the research can contribute to support a proposal for pedagogical action that includes the principle of dialectic between theory and practice in the teaching of Philosophy in Public Schools. DOI:https://doi.org/10.56238/ptoketheeducati-081